Combining Ability Studies In Oats (Avena Sativa L.) For Seed Yield (Applied Biological Research, 2013)
Combining ability studies in oats (Avena sativa L.) for seed yield was carried out to generate information on general and specific combining ability and nature and magnitude of gene effects for seed yield and their attributing traits.  The experimental materials comprized of 10 diverse parents and 45 F1 crosses  (excluding reciprocals) generated through diallel mating design. The  experimental material was evaluated in a randomized complete block design  over 3 locations. Observations were recorded on 4 quantitative characters.  Significant interactions between combining ability effects and environments  were observed for all the traits. The estimates of dominance variance were  higher in magnitude than their corresponding additive genetic variance in  individual as well as pooled analysis indicating preponderance of non-additive  gene action for all traits. Estimate of average degree of dominance revealed  preponderance of over-dominance for all the traits. Parents ‘SKO-207’ and  ‘SKO-208’ were identified as a good general combiner for all the traits viz., spikelets panicle-1, 1000-seed weight, seed length: breadth ratio and seed yield  plant-1. The most promising crosses showing highly positive and significant  SCA effect for seed yield were SKO-211 x SKO-213, SKO-207 x SKO-208,  SKO-210 x SKO-212, SKO-209 x SKO-210, SKO-210 x SKO-213, SKO-208 x SKO-213 and SKO-208 x SKO-211.
Keywords: Avena sativa; combining ability; GCA; SCA; seed yield